2011
DOI: 10.1128/mcb.01071-10
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Antisense Transcription Controls Expression of Cell-Type-Specific Genes in Yeast

Abstract: Transcriptome profiling studies have recently uncovered a large number of noncoding RNA transcripts (ncRNAs) in eukaryotic organisms, and there is growing interest in their role in the cell. For example, in haploid Saccharomyces cerevisiae cells, the expression of an overlapping antisense ncRNA, referred to here as RME2 (Regulator of Meiosis 2), prevents IME4 expression. In diploid cells, the a1-␣2 complex represses the transcription of RME2, allowing IME4 to be induced during meiosis. In this study we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 49 publications
2
113
0
Order By: Relevance
“…Their findings were consistent with a transcriptional interference mechanism, since transcription of Rme2 in haploid cells only interfered with Ime4 sense expression in cis (Hongay et al, 2006). Similarly, Zip2, a meiosis-specific protein involved in synaptonemal complex formation, shows cell-type specific sense and antisense expression (Gelfand et al, 2011). Haploids express an antisense transcript to Zip2, called Rme3 (regulator of meiosis 3) and MAT a/ diploids express Zip2 sense RNA.…”
Section: S Cerevisiae Ime4 and Zip1 Ncrna Functionssupporting
confidence: 66%
See 3 more Smart Citations
“…Their findings were consistent with a transcriptional interference mechanism, since transcription of Rme2 in haploid cells only interfered with Ime4 sense expression in cis (Hongay et al, 2006). Similarly, Zip2, a meiosis-specific protein involved in synaptonemal complex formation, shows cell-type specific sense and antisense expression (Gelfand et al, 2011). Haploids express an antisense transcript to Zip2, called Rme3 (regulator of meiosis 3) and MAT a/ diploids express Zip2 sense RNA.…”
Section: S Cerevisiae Ime4 and Zip1 Ncrna Functionssupporting
confidence: 66%
“…The a1-2 protein heterodimer silences expression of Rme3 in MAT a/ diploids, enabling expression of Zip2. Gelfand et al (2011) expanded on previous research to show that Rme2 extension through the Ime4 promoter region was not required for Ime4 repression and Rme3 does not extend through the entire Zip2 ORF, indicating that both Rme2 and Rme3 do not interfere with TATA-binding proteins or polymerase binding in the promoter regions. Additionally, a 450 bp region within Ime4 was essential for Rme2-mediated repression.…”
Section: S Cerevisiae Ime4 and Zip1 Ncrna Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional genomic elements have been discovered that are able to regulate transcription of nearby genes through the generation of noncoding RNAs (e.g., see Hongay et al 2006;Houseley et al 2008;Pinskaya et al 2009;Gelfand et al 2011;van Werven et al 2012;Castelnuovo et al 2013), and, based on the finding that noncoding RNA synthesis appears to be a widespread phenomenon in budding yeast (David et al 2006;Neil et al 2009;Xu et al 2009), many more such regulatory examples are likely to be identified in the future.…”
Section: S Cerevisiae Genome Organizationmentioning
confidence: 99%